High‐resolution microendoscope imaging of inverted papilloma and normal sinonasal mucosa: evaluation of interobserver concordance. Issue 12 (30th July 2015) - Parasher, Arjun K.; Kidwai, Sarah M.; Schorn, Victor J.; Goljo, Erden; Weinberg, Alan D.; Richards‐Kortum, Rebecca; Sikora, Andrew G.; Iloreta, Alfred Marc; Govindaraj, Satish; Miles, Brett A.
Abstract : Background: High‐resolution microendoscopy (HRME) enables real‐time imaging of epithelial tissue. The utility of this novel imaging modality for inverted papilloma has not been previously described. This study examines the ability of otolaryngologists to differentiate between images of inverted papilloma and normal sinonasal mucosa obtained with a HRME. Methods: Inverted papilloma and normal sinonasal mucosa specimens were stained with a contrast agent, proflavine. HRME images were subsequently captured. Histopathological diagnosis was obtained for each sample. Quality‐controlled images were used to assemble a training set. After reviewing the training images, 6 otolaryngologists without prior HRME experience reviewed and classified test images. Results: Five samples of inverted papilloma and 2 normal sinonasal mucosa samples were collected. Four representative images from each specimen were used for the 28‐image test set. The mean accuracy among all reviewers was 89.9% (95% confidence interval [CI], 84.3% to 94.0%). The sensitivity to correctly identify inverted papilloma was 86.7% (95% CI, 79.2% to 92.2%), and the specificity was 92.9% (95% CI, 89.0% to 100.0%). The Fleiss kappa interrater reliability score was 0.80 (95% CI, 0.70 to 0.89). Conclusion: Inverted papilloma and normal sinonasal mucosa have distinct HRME imaging characteristics. Otolaryngologists can be successfully trained to distinguish between inverted papilloma and normal sinonasal mucosa. HRME is a feasible tool for identification of inverted papilloma. By conducting future in vivo trials, HRME potentially may enable real‐time surgical margin determination during surgical excision of inverted papilloma.